Comparison of triple (2RHZ/4RHZ) versus quaduple (2RHZE/4RH) drug treatment for tuberculosis in the Philippines a multi-center study - Yu, Charles
OBJECTIVES: To compare the efficacy and effectiveness of triple (2RHZ/4RH) versus quadruple (2RHZE/4RH) drug therapy in terms of: 1) Sputum AFB smear and culture conversion at 2,4,8, & 24 weeks 2) relapse rates at 1and 2 years. 3) radiologic improvement and resolution at 2,6, 12 months. 4) relief of symptoms.5) adverse drug reactions. 6) compliance rates. PATIENTS: 221 evaluate newly diagnosed PTB patients (107 in 3 drug group, 114 in 4 drug group) of which 179 have completed 6 months short course treatment (90 in 3DG & 89 in 4DG). SETTING: Multi-center study covering Cavite, Cebu, Dagupan in Pangasinan, Apalit, Pampanga, Palawan, Davao and Metro Manila. RESEARCH DESIGN: Randiomized controlled, multi-center clinical trila. INTERVENTION: 3 drug group (3RHZ/4RH) served as the control compared to 4DG (2RHZE/4RH) as treatment group. ANALYSIS: Baseline characteristics of dichotomous outcomes were analyzed using chi-square test, ANOVA/t-test were used for the quantitative characteristics. Kappa, ARR and NNT were estimated at 95% confidence level. Survival analysis for symptoms and time to disappearance of symptoms were also done. Power and multiple logistic regression analysis were also utilized. Outcomes were evaluated for efficacy and intention to treat analysis. Compliance rates were compared. Sensitivity analysis were also assuming different scenarios for patient yet to be recruited. RESULTS: A total of 221 (107 in the 3 drug group and 114 in the 4 drug group) were recruited from 7 sites. Comparison of patient characteristics on entry showed no significant difference in mean age, 36.1 vs 37.3, M/F ratio (M/F 1.6 against 1.5) sputum AFB smear & culture status and extent of radiological lesions. Over-all smear positivity was 66.9%, over-all culture positivity was 34.4%. Results from the efficacy analysis of sputum AFB smear conversion at 2,4, and 8 weeks betwen the 3 versus 4 drug group showed no statistically significant difference. (at p values >0.05) with all converting by 6 months in both groups. Among culture positive cases, there was no significant difference at 8 & 24 weeks, with 96.3% conversion at 8 weeks for the 4 drug regimen versus 100% for the 3 drug regimen. At 6 months both groups had 100% conversion. MDR was 9.7%. Fully-senstive organisms was 74.2%. Resistance to at least INH was 21% resistance to at least rifampicin was 8.6%. Comparison radiological films showed that there was no statistical and clinically significant difference between 3 versus 4 drugs at 2 months (90.2% 3DG versus 92.6% fro 4Dg) and at 6 months (80.9 in 3DG vs 86.3 in 4 DG%). There was no significant difference as far as symptom relief was concerned with mean average of 4 weeks for relief of both hemoptysis & fever (95% C.I. 3,5) and 14 weeks (95% CI, 13,16) for 3DG and 16 weeks (95% CI, 14,18) for the 4DG for cough relief. Over-all drop out rate was 6.7% (12/179) among those who had completed 6 months of treatment so far with 7.8% (7/90) in the 3DG and 5.6% in the 4DG (5/89). Compliance rates were comparable with 92.2% for 3DG and 94.4% for 4DG. There were 2 deaths, 1 each for 3DG and 4DG. Intention-to-treat analysis showed failure rate of conversion at 11% for the 3DG and 7% for the 4DG for AFB smear conversion at 6 months and 15% and 18% respectively at 2 months. For AFP culture conversion, it was 28% versus 19%, for the3 DG and 4DG at 6 months and 21% versus 12% at 2 months. NNT for AFB smear conversion at 6 months is 25 (95% CI, 17,7). CONCLUSIONS: At the end of 20 monoths period of study, there is no statistical difference between 3DG and 4DG as far as bacteriologic, radiological and symptoms outcomes parameters. Cure rates and compliance rates (89 vs 93% and 92.2 vs 94.4) as comparable. Sensitivity analysis shows that the trends can still be altered assuming the percent efficacy assumed will be sustained by the renmaining subjects to be recruited. Relapse rates at 1 year follow-up are still too few to be significant. Power analysis shows 86% and 99% to detect a 15% and 20% difference betweern the 2 groups for AFB smear conversion at 6 months and power of 34% and 64% for AFB culture conversion at 6 months. For radiological outcomes at 6 months, power is 85% and 99% respectively to detect 15% and 20% difference between the 2 treatment groups.
Theses--(Master in Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Antitubercular Agents; Tuberculosis, Multidrug-Resistant.